ORÇAMENTO E POLÍTICAS SOCIAIS: metodologia de análise na perspectiva crítica - Evilasio Salvador (Universidade Federal do Maranhão, 2014)
Given the suffered difficulties by the social protection in exacerbation times of the capital crisis this article has as principal goal to show a methodology of critical analysis of the public budget in addition the traditional manual of public finance. The article is organized in four sections. The first section evidences the concept of public fund and public budget, emphasizing the active presence of public resource in the scope of the productive accumulation and the assurance of social policy. The second section shows relevant criteria for the analysis of budget expenditures, especially social spending. The third section addresses the financing of social policies in the critical perspective that seeks an analysis of all costs of the social spending. In the end, highlights the importance of the democratic control of the budget and the public fund. It is an analytical perspective corroborates with the delineation of trends about the condition of social and human rights.